2021
DOI: 10.4149/neo_2020_200411n388
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CDCA3 expression inhibits tumor formation in pancreatic cancer

Abstract: Downregulation of cell division cycle-associated 3 (CDCA3) markedly inhibited cell growth and induced apoptosis in tumors. However, the effect of CDCA3 in pancreatic cancer (PAC) was rarely investigated. Therefore, this study attempted to clarify the role of CDCA3 in PAC. The mRNA and protein expression of CDCA3 were examined in PAC cell lines and tumor tissues by using real-time quantitative PCR (RT-qPCR), western blotting (WB), and immunohistochemistry (IHC). The effects of CDCA3 downregulation on cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Hu et al 38 found that the increased NUF2 expression in PAAD and determined that NUF2 could alter the proliferation and apoptosis of PAAD cell lines through LncRNA-AF339813. Zou et al 39 revealed that CDCA3 expression was increased in the PAAD cell lines compared to normal human pancreatic duct epithelial cells, suggesting that knocking down CDCA3 can inhibit cell proliferation and promote cell apoptosis. Wang et al 40 revealed increased CDCA2 expression in PAAD tumors, and univariate analysis showed that increased CDCA2 expression is a risk factor for PAAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al 38 found that the increased NUF2 expression in PAAD and determined that NUF2 could alter the proliferation and apoptosis of PAAD cell lines through LncRNA-AF339813. Zou et al 39 revealed that CDCA3 expression was increased in the PAAD cell lines compared to normal human pancreatic duct epithelial cells, suggesting that knocking down CDCA3 can inhibit cell proliferation and promote cell apoptosis. Wang et al 40 revealed increased CDCA2 expression in PAAD tumors, and univariate analysis showed that increased CDCA2 expression is a risk factor for PAAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous have determined that CDCA3 expression levels are increased in tumor tissues and associated with a poor patient prognosis in CRC, GC, NSCLC, OSCC and PAC (13)(14)(15)(16)(17)(18). In CRC, CDCA3 regulates E2F transcription factor 1, thereby inhibiting the expression of p21.…”
Section: Discussionmentioning
confidence: 99%
“…CDCA3 regulates cell cycle processes and serves a role in triggering mitosis entry. CDCA3 is frequently upregulated in tumor tissues and is associated with the oncogenic properties of a variety of cancers, including colorectal cancer (CRC) (13,14), gastric cancer (GC) (15), non-small cell lung cancer (NSCLC) (16), oral squamous cell carcinoma (OSCC) (17) and pancreatic cancer (PAC) (18). It has also been reported that CDCA3 acts as a downstream target gene of HOXB3, which promotes prostate cancer progression (19).…”
Section: Suppression Of Cdca3 Inhibits Prostate Cancer Progression Via Nf-κb/cyclin D1 Signaling Inactivation and P21 Accumulationmentioning
confidence: 99%
“…CDCA3 can regulate E2F1 expression to influence growth and progression [31]. Many studies have elucidated the role of CDCA3 expression in diverse tumors; for instance, CDCA3 inhibits the formation of tumors by affecting cell growth and inducing apoptosis in pancreatic cancer [32]. CDCA3 expression affects other cancers as well, such as renal cell carcinoma [33], breast cancer [34], acute myeloid leukemia [35], and non-small-cell lung cancer [5].…”
Section: Discussionmentioning
confidence: 99%